2015
DOI: 10.1016/j.jeurceramsoc.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

On the fabrication of ZrC x N y from ZrO 2 via two-step carbothermic reduction–nitridation

Abstract: This study examined the processing parameters of a two-step carbothermal reduction-nitridation of ZrO 2 as a UO 2 /PuO 2 simulant to fabricate ZrN. Variables studied were the reaction time, reaction temperature and the starting powder composition Higher temperatures, longer reaction times and higher initial amounts of carbon in the starting material lead to increased nitridation similar to previous work with uranium oxide but that reaction rate decreases with time. SEM and TEM of the reacted powders reveal reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…This might be because the carbon from graphite-rich sintering environment at 1700 • C could diffuse into ZrN to form ZrC x N y and thus lead to the slight peaks shift toward lower angles. Previous study has shown that the peaks of ZrC x N y shifted slightly to lower angles with the increase of carbon content [18].…”
Section: Chemical Reactivity Of Si 3 N 4 -Zrb 2 Ceramics Under N 2 Atmentioning
confidence: 78%
“…This might be because the carbon from graphite-rich sintering environment at 1700 • C could diffuse into ZrN to form ZrC x N y and thus lead to the slight peaks shift toward lower angles. Previous study has shown that the peaks of ZrC x N y shifted slightly to lower angles with the increase of carbon content [18].…”
Section: Chemical Reactivity Of Si 3 N 4 -Zrb 2 Ceramics Under N 2 Atmentioning
confidence: 78%
“…В работах [8,9] возможность образования карбонитрида Zr в ходе карботермического восстановления-азотирования оксида ZrO2 изучали по смещению угла дифракции и уширения линий в интервале 2θ от 55 до 75°. На рисунке 3 показана дифрактограмма синтезированных в настоящей работе порошков в сравнении с литературными данными.…”
Section: рисунок 1 -зависимость концентрации O N и C в порошке от врunclassified
“…Рисунок 3 -Дифрактограмма азотированных порошков: а)настоящая работа;б) литературные данные(в скобочках указан режим азотирования в токе азота) [8,9] …”
Section: рисунок 1 -зависимость концентрации O N и C в порошке от врunclassified
“…The carbothermic reduction to nitridation (CTR‐N) process has been used experimentally to produce zirconium oxynitrides as well as high purity zirconium nitride . Although CTR‐N is utilized both in the laboratory and industrially to produce numerous mononitride and mixed nitride materials (e.g., uranium mononitride, aluminum mononitride), zirconium provides a simplified reference case in that a single stoichiometric phase exists for the oxide (ZrO 2 ), carbide (ZrC), and nitride (ZrN).…”
Section: Introductionmentioning
confidence: 99%
“…. This final step results in the removal of carbon through the formation of gaseous HCN, producing a carbon‐free product …”
Section: Introductionmentioning
confidence: 99%